THE ROLE OF CARAVANSERAIS IN THE INTERNAL AND EXTERNAL TRADE OF THE BUKHARA EMIRATE - Dilshod, Sharopov (PT. Antis International Publisher, 2025)
Objective: This study investigates the economic and social functions of caravanserais in the Bukhara Emirate, emphasizing their role in facilitating internal and external trade, supporting merchant activity, and contributing to the economic infrastructure during the 18th–19th centuries. Method: Employing a historical-analytical approach, the research draws upon primary archival sources, travel accounts, and comparative analysis to classify caravanserais by function, examine taxation policies, and reconstruct trade routes. Quantitative data are utilized to assess the growth and economic impact of these structures on urban development and international commerce. Results: The findings reveal that by the 19th century, Bukhara’s caravanserais had evolved into essential trade and financial hubs, with over 60 establishments serving as centers for goods storage, merchant accommodation, and tax collection. Their expansion paralleled increasing trade with Russia, facilitating Bukhara’s integration into regional and global markets. Novelty: This study contributes a systematic classification of caravanserais and unveils their specialized economic roles, offering new insights into taxation systems, urban planning, and transnational trade networks. It presents a recontextualized understanding of caravanserais as dynamic instruments of economic policy and infrastructure in Central Asia.